EFIKASI INSEKTISIDA BERBAHAN AKTIF CYPERMETHRIN DENGAN METODE LETHAL OVITRAP TERHADAP Aedes aegypti DI LABORATORIUM - Zumrotus Sholichah; Tri Ramadhani; Adil Ustiawan (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2010)
Various vector control efforts have been done but dengue hemorrhagic fever still tends to increase. Lethal Ovitrap (LO) was modification from ovitrap where in lethal ovitrap installed ovistrip contain insecticide. The aim of this research was to determine efficacy Cypermethrin and determine the residual effect with lethal ovitrap method on Ae. aegypti at laboratory. This research was laboratory experiment with postest only control group design. Research was done in August-December 2009 at Loka Litbang P2B2 Banjarnegara laboratory. Activity that had been done i.e: colonization of A e. aegypti, making ovitrap, making ovistrip with active ingredient Cypermethrin, then pretest had been done and determine the residual effect. Efficacy analysis used WHO criteria, i.e death of the mosquito >70% after raising for 24 hour.